ANTIOXIDANT ACTIVITY,TOTAL PHENOL,FLAVONOID,ALKALOID,TANNIN AND SAPONIN CONTENTS OF LEAF EXTRACTS OF SALVINIA MOLESTA D.S.MITCHELL - tg, Nithya; J, Jayanthi; Mg, Ragunathan (Asian Journal of Pharmaceutical and Clinical Research, 2016)
Abstract Objective:The main aim of the study was to screen leaf extracts of Â Salvinia molesta ,a fresh water weed to evaluate the antioxidant activity and also Â to quantify total phenol,flavonoid,alkaloid.tannin and saponin contents in order to find possible sources for future novel antioxidants in food and pharmaceutical formulations. Methods:Qualitative and quantitative analyses ofÂ significant phytochemicals were performed by standard methods.The antioxidant activity was evaluated using extracts of aqueous, ethanol, methanol, chloroform and petroleum ether by DPPH assay.Butylated Hydroxy Toluene (BHT), Gallic acid (GA) and Quercetin (Q) were taken as standard. Results:Among the five different solvents, maximum antioxidant activity of salvinia molesta was found in ethanolic extract (90.3%) followed by other solvents.Total phenolic content measured by Folin-Ciocalteau method was 9.84 mg Gallic Acid Equivalents (GAE)/g and the total flavonoid contents as measured by aluminium chloride method was 10.89 mg Quercetin Equivalents (QE)/g.Alkaloids,tannins and saponins were measured by standard methods and found in significantly high ranges exhibiting a rich source of phytochemical constituents ensuring the plant as a useful therapeutic agent. Conclusion:Salvinia molesta a fast growing fresh water weed,also abundantly available in nature possess significant antioxidant activity and hence can be used as an potent therapeutic agent. Â Key words : Salvinia molesta, antioxidant activity, Total phenol ,Flavonoid,Alkaloid,Tannin and Saponin. Â